The Role of Hair Transplantation for Managing Facial Trauma - Epstein, Jeffrey S.; Kuka, Gorana (Facial Plastic Surgery, 2017)
Oftentimes, multiple treatment modalities are indicated for the management of trauma to the face. When this trauma involves a hair-bearing area, such as the eyebrow, eyelid, or beard region, hair transplantation can be an effective modality. While most of these facial hair transplants are performed for elective cosmetic indications, advanced techniques of hair transplantation can assure aesthetic outcomes in the optimizing of appearance after trauma. Because hair regrowth requires a good recipient bed, adjuvant therapies to promote vascularization, such as fat transfer and platelet-rich plasma, can be applied in conjunction with hair transplantation. The authors review the indications and the essential techniques of graft harvesting by follicular unit extraction and follicular unit grafting, and recipient site formation and graft planting and management, and present different case examples illustrating these technique.
Keywords: eyebrow transplantation; eyelash transplantation; beard transplantation; follicular unit extraction; autologous fat transfer